Fine Structure and Optical Features of the Compound Eyes of Adult Female Ceratosolen gravelyi (Hymenoptera: Agaonidae) - Hua Xie; Yan Shi; Shouxian Zhang; Yonghui Zhu; Subo Shao; Yuan Zhang; Pei Yang; Zongbo Li (Insects, 2025)
Pollinating fig wasps (Agaonidae) engage in an obligate mutualism with Ficus species, which is mediated by host-specific chemical cues. However, the role of visual perception in host recognition remains poorly understood, particularly because of a lack of structural studies of their compound eyes. We investigated the ocular morphology of female Ceratosolen gravelyi (exclusive pollinator of F. semicordata) using scanning/transmission electron microscopy. The oval apposition eyes contain 228–263 ommatidia, which are asymmetrically distributed between the left and right eyes. Each ommatidium comprises a biconvex corneal lens overlying a tetrapartite eucone crystalline cone; proximal cone cells reveal an interlaced labyrinth. Pigment cells encapsulate each ommatidium, and numerous pigment granules and mitochondria are present in both pigment and retinular cells. Nine retinular cells comprise a unit, with eight photoreceptors (R1–R8) forming the rhabdom from the cone base to the basal matrix; a ninth cell replaces R8 in the apical third of the rhabdom. Optical metrics, including F-number (1.1°), acceptance angle (10.0°), and ommatidial sensitivity (0.26 µm2/sr), indicate diurnal activity in bright environments. These adaptations suggest that their eyes are critical for processing visual cues during host interactions, which advances our understanding of multimodal sensory integration in fig–wasp mutualism.